"TRAINING OF HIGHLY QUALIFIED VETERINARY PHARMACISTS IN THE FIELD OF VETERINARY MEDICINE" (Intent Research Scientific Journal, 2023)
In this state, the training of highly qualified personnel in the field of veterinary pharmacy is studied. Uchityvaya situatsiyu, vozniyushchuyu and proizvodstve veterinary medicine, meeting all national and international standards.